Addressing Non-linear System Dynamics of Single-Strand RNA Virus–Host Interaction - Romano, Alessandra; Casazza, Marco; Gonella, Francesco (Frontiers in Microbiology, 2021)
Positive-single-strand ribonucleic acid ((+)ssRNA) viruses can cause multiple outbreaks, for which comprehensive tailored therapeutic strategies are still missing. Virus and host cell dynamics are tightly connected, generating a complex dynamics that conveys in virion assembly to ensure virus spread in the body. Starting from the knowledge of relevant processes in (+ss)RNA virus replication, transcription, translation, virions budding and shedding and their respective energy costs, we built up a Systems Thinking (ST)-based diagram of the virus-host interaction, comprehensive of stocks, flows and processes as well-described in literature. In ST approach, stocks and flows are expressed by a proxy of the energy embedded and transmitted, respectively, while processes are referred to the energy required for the system functioning. In this perspective, healthiness is just a particular configuration, in which stocks relevant for the system (equivalent but not limited to proteins, RNA, DNA and all metabolites required for the survival) are constant and the system behavior is stationary. At time of infection, the presence of additional stocks (e.g. viral protein and RNA and all metabolites required for virion assembly and spread) confer a complex network of feedbacks leading to new configurations, which can evolve to maximize the virions stock, so changing the system structure, output and purpose. The dynamic trajectories will evolve to achieve a new stationary status, a phenomenon described in microbiology as integration and symbiosis when the system is resilient enough to the changes, or the system may stop functioning and die. Application of external driving forces, acting on processes, can affect the dynamic trajectories adding a further degree of complexity, that can be captured by ST approach, used to address these new configurations. Investigation of system configurations in response to external driving forces acting are be developed by computational analysis based based on ST-diagrams, with the aim at designing novel therapeutic approaches.